Pengaruh Self-Efficacy terhadap Subjective Well-Being pada Mahasiswa Yang Sedang Skripsi di Jurusan Psikologi UNP - Widiana, Wila; Rusli, Devi (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
This is study aims to look at the effect o self-efficacy on subjective well-being in student who are doing undergraduate thesis in the psychology departement of UNP. The design used in this study is quantitative. The number of subjects in this study were 100 UNP psychology students. The sampling technique used is purposive sampling. The isntrument in this study is a Likert scale. Data collection was performed using a scale of self-efficacy and subjective well-being. Data were analyzed using simple linear regression analysis techniques. Based on the results of hypothesis testing obtained p=0,000 (p<0,05), this means that there is a undergrate thesis in the departement of Psychology UNP